2021
DOI: 10.1016/j.ebiom.2021.103525
|View full text |Cite
|
Sign up to set email alerts
|

Identification of COVID-19 prognostic markers and therapeutic targets through meta-analysis and validation of Omics data from nasopharyngeal samples

Abstract: Background While our battle with the COVID-19 pandemic continues, a multitude of Omics data have been generated from patient samples in various studies. Translation of these data into clinical interventions against COVID-19 remains to be accomplished. Exploring host response to COVID-19 in the upper respiratory tract can unveil prognostic markers and therapeutic targets. Methods We conducted a meta-analysis of published transcriptome and proteome profiles of respiratory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 76 publications
1
28
0
1
Order By: Relevance
“…First, S100 calcium-binding proteins and LRRK2 are known to promote inflammation and cytokine production [40][41][42][43][44] . In fact, an increase of S100 calcium-binding proteins has been reported in severe or critically ill COVID-19 patients 45,46 . Furthermore, treatment with paquinimod, a selective inhibitor of S100A8/ A9, prevented death in a lethal model of mouse coronavirus infections 47 .…”
Section: Resultsmentioning
confidence: 99%
“…First, S100 calcium-binding proteins and LRRK2 are known to promote inflammation and cytokine production [40][41][42][43][44] . In fact, an increase of S100 calcium-binding proteins has been reported in severe or critically ill COVID-19 patients 45,46 . Furthermore, treatment with paquinimod, a selective inhibitor of S100A8/ A9, prevented death in a lethal model of mouse coronavirus infections 47 .…”
Section: Resultsmentioning
confidence: 99%
“…With encouraging results of in vivo efficacy against IAV, we next tested the same against SARS-CoV-2. For this, we used the Syrian Golden hamster model and an optimized protocol for testing antivirals against SARS-CoV-2 developed by our group (Fig 3A) (Biji et al, 2021). We observed that IP administration of 20 mg/kg PA prophylactically and therapeutically, resulted in a reduction of lung vRNA load on D3 post-infection by ∼3 and ∼1 order of magnitude respectively (Fig 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Despite progress in understanding the pathogenesis of COVID-19, the development of vaccines, and increasing experience in managing patients, COVID-19 remains a critical healthcare problem worldwide. While intense efforts to understand and predict the differential impact of SARS-CoV-2 infection on individuals have resulted in an expanding trove of data on gene, protein, and cellular processes in patients with COVID-19, front-line care of patients still focuses on the use of practical, well-understood, and easily automated routine laboratory tests [ 8 , 14 , 15 , 16 ]. The strong inflammatory component of COVID-19 has led to interest in measuring cytokines such as IL-6, as well as other differentially expressed biomarkers, but these assays are not routinely available in clinical laboratories [ 17 ].…”
Section: Discussionmentioning
confidence: 99%